Designing effective speech interfaces - Susan Weinschenk (John Wiley & Sons, 2000)
This book discusses the basics of speech interfaces and speech technology, hardware, and software. It clearly explains the interface design principles that are applied to S/GUI and AUI interfaces and describes the lastest practices of experts.